Filmy aktorskie o przygodach Asteriksa i Obeliksa jako przejaw obecności antyku we współczesnej kulturze audiowizualnej - Stawiski, Maciej (Collectanea Philologica, 2015)
The films with actors about the adventures of Asterix and Obelix are an important part of the contemporary popular culture. The plot of these film is located in antiquity therefore ancient motives are common in them. It is very important to check if these motives are showed in the way which is consistent with historical truth. And it is very important to know how big their influence on popular perception on antiquity is. This article is a first step to answer these questions. It shows that some motives are showed correctly but some are presented incorrectly. It suggests also that some people may see druids through the prism of these films.